AKIBAT HUKUM TERHADAP PEMBATALAN PERKAWINAN YANG DILAKUKAN ISTRI PERTAMA BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Febby Olivia (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT This research is entitled as a result of the law on the cancellation of marriage which was carried out by the first wife based on Law No. 1 of 1974 concerning Marriage. The purpose of this study is to find out how the impact of marital status in the cancellation of marriage and the legal consequences caused to children and property.The impact of the status of the marital cancellation was calculated from the date the decision of the Religious Court was dropped and the decision had a permanent legal force and was valid from the time the marriage took place.The marriage that was deemed to have been broken or never existed and the parties who canceled the marriage returned to their original status because the marriage was deemed to have never existed and the parties had no legal relationship.In the event of a marriage cancellation, the child born of the marriage requested for cancellation remains the responsibility of both parents as before the marriage is canceled. This responsibility will last until the child is mature. Responsibilities include the cost of daily living and education   Keywords: cancellation of marriage by first wife, Marriage Act